The Influence of Media on Dressing Pattern of Tertiary Institution Student in Nigeria - Abdullahi, Shehu Abdulkadir (Lembaga Yasin AlSys, 2024)
The study titled “media influence on dressing pattern of students of tertiary institutions. The aimed of the study is to discover the influence of home movie in dressing pattern of students in higher institutions of learning. To identify if there is influence on the dressing pattern of students of tertiary institutions in Nigeria, To determine the nature of the influence on their dressing patterns, To know if the influence is positive or negative and To explore ways that can positively influence their dressing patterns. The study adopted Cultivation and Cultural imperialism theories and survey method approach. The data of the study were sourced from the primary sources. The instrument used for data collection was the closed ended questionnaire. 370 questionnaires were administered to respondents. The findings of the study revealed that dressing patterns in home media have positive Influence on the dressing style of students. This is manifested in the pride these students derive in seeing African values celebrated as reflected in their dress patterns. The study showed that most of these students expose themselves to the home movie medium and even a higher percentage do so at regular basis and are more prone to noticing the dress patterns on those home movie. The home media are therefore veritable instruments for mobilization and national orientation for desirable attitudes.